Charalambos Papastathis, The Statute of the Athonic Russian cells’ brotherhood according to the constitutional laws of Mount Athos, Sofia (ανάτυπο από τα Actes du Prémier Congrès International des Études Balkaniques et Sud-Est Européennes, τόμ. IV, Histoire) - Παπουλίδης, Κωνσταντίνος Κ. (Μακεδονικά, 2015)
No abstract